Lung cancer in relation to employment in the electrical utility industry and exposure to magnetic fields. - Savitz, D A (1997)
OBJECTIVES: A recent study found that lung cancer may be associated with exposures encountered in the electrical utility industry. To further evaluate this possibility, data were collected and analysed from five large electrical utility companies in the United States. METHODS: A cohort of 138905 male workers employed between 1950 and 1986 was followed up for mortality to the end of 1988, with 20733 deaths identified of which 1692 were due to lung cancer. Mortality from lung cancer was examined in relation to the duration of employment in specific jobs thought to have high exposure to 60 Hz magnetic fields and to an index of cumulative exposure to magnetic fields based on personal measurements. Exposure to pulsed electromagnetic fields (PEMFs) as estimated from another study was also considered. Poisson regression generated rate ratios for categories of exposure based on comparisons within the cohort adjusted for age, calendar year, race, socioeconomic status, work status, and estimated exposure to asbestos. RESULTS: Mortality rose modestly with duration of work as an electrician or power plant operator reaching rate ratios of 1.4 with > or = 20 years in those jobs but not with duration of work as a lineman or a combination of jobs thought to have high exposures to 60 Hz magnetic fields or PEMFs. Cumulative indices of exposure to 60 Hz magnetic fields and PEMFs were both associated with rate ratios of 1.2-1.3 in the highest intervals. CONCLUSIONS: These data suggest that lung cancer is not strongly associated with duration of employment in specific jobs associated with high potential exposure to 60 Hz magnetic fields or to PEMFs. Small associations of lung cancer with indices of both 60 Hz magnetic fields and PEMFs leave open the possibility that larger associations have been diluted through exposure misclassification. Refined exposure assessment, especially to PEMFs, would be required to evaluate that possibility.